Effect of container color on substrate temperatures and growth of red maple and redbud - Markham, John W., III; Bremer, Dale J.; Boyer, Cheryl R.; Schroeder, Kenneth R. (My University, 2013)
Heat stress is problematic to root growth in the production of containerized nursery plants. Container color may moderate effects of solar radiation on substrate temperatures. Studies were conducted near Manhattan, KS, to evaluate effects of container color on growth of roots and shoots in bush beans (Phaseolus vulgaris L.), red maple (Acer rubrum L.), and eastern redbud (Cercis canadensis L.). Four treatments among studies included containers colored flat and gloss white, silver, and black; a green container color treatment was added to the tree studies. Plants were grown in bark-based soil-less substrate and temperatures were measured at 5-cm depths in the south sides and centers. After 4 months, plant variables were measured. Roots were separated into three sections: core, north, and south. In the bean study, substrate temperatures at the south side of the container averaged lowest in flat and gloss white (≈36 °C) and greatest in black containers (50.3 °C). Root density at the south side was reduced in beans by 63% to 71% in black compared with flat and gloss white. In heat-sensitive maples, substrate temperatures at the south side of containers averaged up to 7.7 °C greater in black and green than in other treatments. Substrate temperatures in the center averaged 3.5 to 3.8 °C greater in black than in flat and gloss white, resulting in up to 2.5 times greater root density in flat and gloss white than in black containers. In heat-tolerant redbuds, the effects of container color on whole-plant growth were less evident. Data suggest that heat-sensitive plants benefit from being grown in white containers or painting outer surfaces of green and black containers white.
Keywords: Acer rubrum; Cercis canadensis; Heat stress; Nursery production; Phaseolus vulgaris; Redbud; Red maple